Analisis Strategi Pemasaran dalam Meningkatkan Penjualan pada CV Hj. Mbok Sri Palu - Sri Ayu Suci Maharani; Zakiyah Zahara; Asriadi; Ira Nuriya Santi (MES Bogor, 2023)
In the current era of digitalization, it is very important for entrepreneurs to be adaptive and creative in attracting customer purchases to increase sales results. Sales can increase by implementing various marketing strategies, such as online marketing, promotions, and so on. CV Hj. Mbok Sri Palu is a business engaged in souvenirs typical of the Palu region. This study aims to analyze marketing strategies in order to increase sales on CV Hj. Mbok Sri Palu. This study used descriptive qualitative research method. The data sources used are primary data sources and secondary data with data collection methods using observation, interview and literature studies or literature reviews. The results of this study prove that CV Hj. Mbok Sri Palu implements marketing strategies, including providing offline and online purchase services, looking for quality material suppliers, providing friendly and polite service to customers, holding promotions through social media and marketplaces, providing discounts to customers who make purchases in large quantities, providing a comfortable and clean rest area so that buyers who visit the center CV Hj. Mbok Sri Palu souvenirs can enjoy a break from travel as well as shopping for souvenirs.